â€œANALISIS KEBIJAKAN CSR TERHADAP KESEJAHTERAAN MASYARAKAT DI MOJOKERTO TAHUN 2011â€ (STUDY KASUS PADA BANK JATIM CABANG MOJOKERTO) - JUSTICE, ANISA (Jurnal Akuntansi AKUNESA, 2013)
Bank Jatim is one of state owned corporations who does corporate social responsibilitythat focuses on four areas including education, culture, health and social. The purpose of thisjournal is to know the Bank Jatim’s CSR policy and the effect for prosperity publik in Mojokerto.This research use qualitative descriptive method. Objects of the research are Bank Jatim branchMojokerto and public around Mojokerto, the technique of collecting data by interviews andobservations. The result of this research showing that Bank Jatim’s CSR policy branchMojokerto in social area are giving free camp for cadger and occupancy improvement. Thepolicy have an impact to cadger income and security at home that has been repaired.Key words: Bank Jatim’s CSR policy, Corporate Social Responsibility, prosperity public